2009
DOI: 10.1002/ar.20901
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐beta1 and TGFBR1 are Expressed in Ameloblasts and Promote MMP20 Expression

Abstract: Transforming growth factor-beta (TGF-beta) signaling exerts a wide spectrum of biological functions. To investigate TGF-beta signaling in amelogenesis, we initially assessed the expression of TGF-beta1 and TGF-beta receptor 1 (TGFBR1) in developing teeth by immunohistochemistry. Both TGF-beta1 and TGFBR1 were strongly expressed in secreting ameloblasts. Next, we studied the effects of TGF-beta signaling on the expression of MMP20 and KLK4 mRNA using ameloblast-lineage cells (ALC) in vitro. Our RT-PCR study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…In contrast, Gao et al (2009) showed that for ALCs, TGF-β1 did not induce KLK4 expression but did induce MMP20 expression. In their study, MMP20 and KLK4 transcript levels were assessed by performing reverse transcription PCR with scanning of the resulting bands for quantification of gene expression.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, Gao et al (2009) showed that for ALCs, TGF-β1 did not induce KLK4 expression but did induce MMP20 expression. In their study, MMP20 and KLK4 transcript levels were assessed by performing reverse transcription PCR with scanning of the resulting bands for quantification of gene expression.…”
Section: Discussionmentioning
confidence: 83%
“…is expressed in ameloblasts of developing enamel (Gao et al, 2009). Interestingly, the tooth development in TGF-b1 mutant mice is unaffected, which could be partially due to rescue by maternal TGF-b1 (D'Souza and Litz, 1995).…”
Section: -Fold) In the Enamel Organs Of Itgb6mentioning
confidence: 99%
“…Reportedly, TGF-β is present in the inner enamel epithelium and cervical loop, is involved in tooth morphogenesis, regulates secretory ameloblast differentiation 14) , and promotes amelogenin and enamelysin secretion 20), 21) . In our study, TGF-β-R1, Smad3, and p-Smad3 showed strong or strongest positive reactions in the inner enamel epithelium, cervical loop, and secretory ameloblasts, and the reactions of Smad3 and p-Smad3 were particularly strong in the cell nuclei in the inner enamel epithelium.…”
Section: Ameloblasts and The Wnt And Tgf-β β β β β Signaling Pathwaysmentioning
confidence: 99%